Oral Fluoroquinolones in the Treatment of Pneumonia, Bronchitis and Sinusitis. (1st October 2002) - Mittmann, Nicole; Jivraj, Farah; Wong, Angelina; Yoon, Alice
Abstract : BACKGROUND: Despite a relatively large number of clinical studies comparing oral fluoroquinolones to one antibiotic class comparator, there is limited information on the relative efficacy of different fluoroquinolones. OBJECTIVE: To examine the efficacy and tolerability of oral fluoroquinolones in the treatment of mild to moderate community-acquired pneumonia, acute exacerbations of chronic bronchitis and sinusitis. METHODS: A systematic review was undertaken with a MEDLINE search for antibiotics and indications. Included studies met the following criteria: original study; random allocation to treatment groups; treatment with one of the following oral antibiotics - moxifloxacin, levofloxacin, ciprofloxacin, gatifloxacin; controlled by either placebo or an active comparator medication; double-blind, single-blind or open treatment; men and women (18 years of age and older); diagnosis of one of the three indications; and treatment duration of at least three days. Outcome measures included efficacy and safety. Comparative and single arm meta-analyses were conducted. Statistical differences in antibiotic success rates were evaluated. Pooled point estimates and 95% CIs for the comparative statistics (z-scores, P-values) and the single-arm analysis were examined to evaluate equivalence. RESULTS: The results of the comparative and single meta-analyses revealed no major differences between the new fluoroquinolones. This is not surprising because the clinical studies were designed to show equivalence versus their comparators. Few comparative evaluations were conducted due to a paucity of studies. In relation to other competitors, small differences were seen. CONCLUSIONS: Results indicate that, in general, fluoroquinolones had similar efficacy, overall safety and dropout rates.